Providing brief information on clinical trials in appropriate formats may improve impressions and willingness to participate among socioeconomically disadvantaged people in France - Salvatore Metanmo; Emilien Schultz; Michele Planta; Sylvain Besle; Julien Mancini (PLoS ONE, 2025)
Background Clinical trial (CTs) participation rates are low worldwide, including in France. One barrier to participation is a lack of familiarity with CTs, especially in socioeconomically disadvantaged populations. We aimed to ascertain whether providing brief information on CTs to these populations could improve their impression of and participation in CTs. Methods We conducted an online cross-sectional survey among socioeconomically disadvantaged adults living in mainland France. The questionnaire included three parts: 1) routine sociodemographic and socioeconomic questions, health-related variables, and questions on health literacy and numeracy, 2) questions on their impression of CTs and their health, and 3) three questions to assess their comprehension of tables. After completing the questionnaire, participants were randomized into three groups that received an information note on CTs in text (one group) or tabular (two groups) format. The content in tabular format was slightly different for both groups. The same CT questions were asked again to assess possible changes in participants’ impression of CTs. Results Among 401 participants, 368 (91.8%) had heard about CTs. Median age of the latter was 40 years, 64% were women, 57% had limited health literacy, and 13% had poor comprehension of tables (score = 0). After reading the brief CT information note, the median CT impression score increased significantly from 5.0 to 6.5 (p-value < 0.001, effect size r = 0.47) within all sub-groups (e.g., according to the comprehension of tables score, according to health literacy level), except for the sub-group with poor comprehension of tables subsequently given CT information in tabular form. Discussion/Conclusion The initial impression of CTs was quite poor in this socioeconomically disadvantaged sample, but improved after the brief information note on CTs was provided. Information campaigns on CTs could help increase CT participation rates among socioeconomically disadvantaged populations. In this perspective, the information format may be just as important as the content.